Effective techniques for the formation of reader competence and their application in the classroom - Zinin, Yevgeniy Olegovich; Rakhimova, Shohsanam (Science and Education, 2023)
In this article, we consider a number of basic principles that underlie the development of techniques for the formation of reader competence among students in the lessons of the Russian language and literature.